An Analysis of the Management Problem of Working Practices of Industry in Vocational High School - Burhan, Muhammad Iswal; Ahmad, Arifin; Alimuddin, Mahmud (International Review of Management and Marketing, 2017)
The purpose of this study is to analyze the problem and the management of working practice of industry in Vocational High School. This research is based on analysis of the factors influencing the management of working practice of industry regarding steps taken in the stages of planning, organizing, implementing, monitoring, and assessing. The researchers applied survey method with descriptive quantitative. The subjects of the research 30 students majoring at the installation of electric power engineering at vocational high school 1 in Minasatene, Pangkajene Islands who have attended the Job Training Industry. Based on the analysis of the data, it is found that the management of working practice of industry for planning phase is generally in the good and very good category. However, there are some problems in term of the determination of target industries so that some indicators are in the poor category. In organizing stage, some indicators about teachers and instructors understanding of job description in the industry are in the poor category. In implementing stage, the indicators of instructors and materials presented in the introduction of industry are in the good category, and there are no problems about these matters. There are still some problems in analyzing the steps and method of evaluation and assessment which put the role of supervisor and instructors. Based on the findings, it is expected that the results can be a reference in developing and improving the management of working practice of industry in Vocational High School so that its implementation can be maximal. Keywords: Problem Management, Working Practices, Vocational High School JEL Classification: I2